Hyperbaric oxygen therapy for thalamic pain syndrome: case report - Slade, John Benjamin; Kwan, Nathan; Lennox, Peter; Gray, Russell (Frontiers in Neurology, 2024)
Introduction: Thalamic pain syndrome is a distressing type of central post-stroke pain (CPSP) that occurs in up to 10% of cases following a cerebrovascular accident, typically with delayed onset of signs and symptoms and often is chronic or even life-long. Thalamic pain syndrome, as is the case for other CPSP, is difficult to treat and response is typically moderate at best. Central pain also occurs after vascular insults in parts of the CNS other than the thalamus. Only a few patients present with the classic "Dejerine and Roussy syndrome" so the term CPSP is preferred to describe neuropathic pain after stroke. There are no pathognomonic features of this syndrome. The thalamus probably has a substantial role in some patients with central pain, either as a pain generator or by abnormal processing of ascending input. Long-term post-stroke pain disorders can reduce quality of life, affect mood, sleep and social functioning, and lead to suicide. Hemi-body pain is common in patients with thalamic lesions. Hyperbaric oxygen has known physiologic and pharmacologic effects with documented benefit in brain-related hemorrhages, acute and chronic stroke, traumatic brain injury, mild cognitive impairment, neurodegenerative diseases, and neuroprotection, but has never been reported as a treatment for thalamic pain syndrome. A 55-year-old male with a history of migraines suffered a right thalamic lacunar infarction following a brain angiogram to investigate a suspected AVM found on prior imaging that resulted in immediate left-sided weakness and numbness evolving to severe chronic pain and subsequent stiffness. Diagnosed thalamic pain syndrome, multiple pharmacologic therapies provided only partial relief for a year after the stroke. The patient's symptoms resolved and quality of life markedly improved with hyperbaric oxygen therapy as assessed by multiple validated questionnaires and may be a treatment option for thalamic pain syndrome.